A Guide to Forensic Accounting Investigation. - Skalak, Steven L.; Golden, Thomas W.; Clayton, Mona M.; Pill, Jessica S. (Hoboken : John Wiley & Sons, 2011)
Recent catastrophic business failures have caused some to rethink the value of the audit, with many demanding that auditors take more responsibility for fraud detection. This book provides forensic accounting specialists & mdash;experts in uncovering fraud & mdash;with new coverage on the latest PCAOB Auditing Standards, the Foreign Corrupt Practices Act, and on options fraud, as well as on fraud in China and its implications. Auditors are equipped with the necessary practical aids, case examples, and skills for identifying situations that call for extended fraud detection procedures.
OBJECTIVES OF ALL INTERESTED PARTIESHOW SHOULD THE INVESTIGATION OBJECTIVES BE DEFINED?; WHO SHOULD DIRECT THE INVESTIGATION AND WHY?; READY WHEN NEEDED; WHERE TO FIND SKILLED FORENSIC ACCOUNTING INVESTIGATORS; Chapter 8: Anonymous Communications; TYPICAL CHARACTERISTICS OF ANONYMOUS TIPS; FEDERAL STATUTES RELATED TO ANONYMOUS REPORTING AND WHISTLE-BLOWER PROTECTIONS; RECEIPT OF AN ANONYMOUS COMMUNICATION; INITIAL UNDERSTANDING OF ALLEGATIONS; DETERMINE WHETHER ANY ALLEGATION REQUIRES IMMEDIATE REMEDIAL ACTION; DEVELOPMENT AND IMPLEMENTATION OF THE INVESTIGATIVE STRATEGY; DISCLOSURE DECISIONS.
Prioritize the allegations.
Includes bibliographical references and index.
Print version record.
Keywords: Forensic accounting; Fraud investigation; Forensic investigation -- Auditing; Fraud investigation -- Auditing; Social Science; Electronic books